The Influence of Taxpayer Knowledge, Tax Sanctions, and Mobile SAMSAT System on the Compliance of Motor Vehicle Taxpayers at Pamulang University - Theresia Mia Novitasari; Intan Rahma Sari (International Journal of Educational and Life Sciences, 2025)
This consider points to decide the impact of citizen information, assess sanctions, and the portable samsat framework on the compliance of engine vehicle citizens at Pamulang College. The populace and test of this think about were 92 respondents from understudies in semesters 4,5, and 6. The information collection handle employments essential information, one existing information is information that's directly obtained from the first information source so that the information gotten reflects the real circumstance or reality. The information utilized is quantitative information sourced from essential information, at that point the collected information is analyzed utilizing graphic investigation strategies, classical suspicion testing, legitimacy, unwavering quality and theory testing.